Pentingnya Pencegahan Narkoba Di Kalangan Pelajar Sekolah Menengah Kejuruan (Smk) Bangun Persada Bekasi - Novita Eleanora, Fransiska; Al Adawiah, Rabiah; Supriyanto, Edy; Heliany, Ina (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The Importance of Drug Prevention Among Students Vocational High School (SMK) Build Persada Bekasi. The rise of drug abuse among students has received serious attention from all parties because it has damaged the nation's future generations. Drugs are very dangerous for anyone who consumes or uses them either because of trial or error or because of an element of intentionality, especially when used in excess, these substances or materials can have very harmful physical and mental consequences and lead to addiction. The research conducted through a literature study conducted on 5 journals, 2 books and 2 online news related to drug prevention in Indonesia. The purpose of community service activities through legal counseling is expected to able provide understanding and awareness for students to avoid drug abuse and understand the legal impact Act. The activity method is carried out using Zoom platform/application to meet face to face with students. The result is that with implementation community service activity, they understand and know impacts and dangers of drugs as well as prevention efforts that must be done to avoid and apply sanctions given to perpetrators and drug users. from early age to students so that they can avoid their use as much possible, and suggestions need to socialize the dangers of drugs and their prevention